The Double Identities of the Shaman and the Dualistic Attitudes of the State: An Exploration of Contemporary Organizational Shamanism in Northeast China - Qu, Feng (Religions, 2024)
This paper presents a case study of the first shamanic organization in China and argues that organizational shamanism in Northeast China is characterized by the double identities of the shaman and the dualistic attitudes of the national authorities. The analyses in this paper reveal how the shamanic organization created a modernized and globalized space for traditional shamans and specialists to connect with the outside world, enabling them to gain empowerment, legitimacy, and agency. Chinese authorities hold dualistic attitudes towards shamanism: the positive attitude of seeing shamanism as part of cultural heritage has always been coupled with the negative attitude of seeing shamanism as superstition. The studies in this paper demonstrate that organizational shamanism in Northeast China has played a crucial role in negotiating with political authorities and linking local traditions with global discourse. In this sense, the traditional eco-cosmological way of maintaining relationships with natural forces and nonhuman beings has been irrevocably transformed into a cosmopolitical form for the shaman, where the animistic world engages with the outside world, global currency, and political forces.